IDENTIFICATION OF CARBIDES AND SIGMA PHASE IN 304 AUSTENITIC STAINLESS STEEL AFTER 24 YEARS OF SERVICE IN AN ETHYLENE PLANT - Evan Reinaldo, Nikolaus
Ethylene is a raw material for several chemicals. Ethylene can be obtained from a thermal cracking process in a furnace consisting of two parts: the convection section and the radiant section. This research is focused on identifying the effect of support pipe in the USSH convection heater, which is made from 304 stainless steel, heating at 510 ? for 24 years. Operating at this temperature for a long time can produce intermetallic and carbide phases, reducing the material's mechanical properties. The specimens were examined for chemical composition using the OES method and etched using a modified Murakami solution to see the specimen's microstructure, especially the sigma phase. The chemical composition of the suspected sigma phase was examined using SEM-EDS. For carbide examination, the specimen was re-etched using NACE TM-0498 solution and KMnO4 + KOH solution. After that, the specimens were also solution annealed at 1100 ? for 2 hours to dissolve the sigma and carbide phases into the austenite matrix. Hardness tests were also carried out to see the effect of the sigma and carbide phases being formed. As a result of operating for 24 years, the delta ferrite phase decomposes into sigma and carbide phases, primarily present in the 50% thickness of the crosssection. A metal-depleted zone layer was formed underneath the surface, due to oxidation after 24 years of operation.